Price rigidities and the granular origins of aggregate fluctuations - Ernosto Pasten; Raphael Schoenle; Michael Weber (Bank of Finland, 2018)
We study the ability of sectoral shocks to generate aggregate fluctuations in a multi-sector general equilibrium model featuring sectoral heterogeneity in price stickiness, sector size, and input-output linkages. We show fat-tailed distributions of sectoral size or network centrality are neither necessary nor sufficient for idiosyncratic shocks to generate aggregate fluctuations when the responsiveness of prices to shocks varies across sectors. We derive conditions under which a frictional origin of aggregate fluctuations arises, that is, when micro shocks contribute to aggregate fluctuations in an economy with heterogeneous price rigidities but equal sector size and network centrality across sectors. We calibrate a 341-sector version of the to the United States and a quantitatively large frictional effect. When we allow for heterogeneities in price rigidity, sector size, and network centrality, the effect of micro shocks on GDP volatility doubles relative to a frictionless economy. Heterogeneity in price rigidity also substantially changes the identity of the sectors from which GDP fluctuations originate.
URN:NBN:fi:bof-201802051159
Keywords: E31; E32; O40; 330